2020
DOI: 10.3390/nu12041179
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acids and Eye Health: Opinions and Self-Reported Practice Behaviors of Optometrists in Australia and New Zealand

Abstract: This study investigated optometrists’ attitudes and self-reported practice behaviors towards omega-3 fatty acids for eye health, and knowledge and understanding of their potential risks and benefits. An anonymous online survey was distributed to optometrists in Australia and New Zealand. Questions included practitioner demographics and practice modality; self-reported practices and recommendations relating to diet, nutritional supplements, and omega-3 fatty acids for age-related macular degeneration (AMD) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…The drug therapy adopted for these pathologies, can be supported by the intake of particular foods or food supplements, which have been shown to be able to address, together with drugs, the pathophysiologic mechanisms directly involved. Numerous micronutrients and nutraceuticals products, in fact, can affect some eye components through the involvement of different metabolic pathways [17][18][19]. This review can be divided into three sections: in the first part, the close correlation between the main pathologies affecting the eye and oxidative damage is described; in the second part, the beneficial effects of some anti-oxidant compounds on eye health are developed; finally, the third section deals with the hypothetical development of an antioxidant mixture, motivating the choice and the age of the people who should take it.…”
Section: Figure 1 Eye Structure and Vision Mechanismmentioning
confidence: 99%
“…The drug therapy adopted for these pathologies, can be supported by the intake of particular foods or food supplements, which have been shown to be able to address, together with drugs, the pathophysiologic mechanisms directly involved. Numerous micronutrients and nutraceuticals products, in fact, can affect some eye components through the involvement of different metabolic pathways [17][18][19]. This review can be divided into three sections: in the first part, the close correlation between the main pathologies affecting the eye and oxidative damage is described; in the second part, the beneficial effects of some anti-oxidant compounds on eye health are developed; finally, the third section deals with the hypothetical development of an antioxidant mixture, motivating the choice and the age of the people who should take it.…”
Section: Figure 1 Eye Structure and Vision Mechanismmentioning
confidence: 99%
“…Optometrists reported recommending omega-3 rich foods for AMD (68%) with 95% recommending fish or non-fish seafood as a source. However, in accordance with the lack of supporting evidence, only 29% recommended specific doses of omega-3 fatty acid supplements to patients [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…An important point to consider is that the studies that were reported recently (2020 and later) [ 50 , 52 , 57 , 62 , 78 ] show that there are improved rates of advice provision amongst practitioners compared to earlier studies [ 35 , 36 , 43 , 45 , 49 , 54 , 55 ]. However, this review highlights that there is still a need for further education for practitioners, specifically about the importance of smoking cessation advice.…”
Section: Discussionmentioning
confidence: 99%
“…The Western diet is characterized by a high intake of saturated fatty acids and low consumption of polyunsaturated fatty (PUFAs) and long-chain PUFAs (LC-PUFAs) [ 142 , 143 , 144 , 145 , 146 ], and for this reason it is considered one of the causes of systemic inflammation. In Western populations, the ratio between omega-6 (one of the factors promoting inflammation) and omega-3 has been estimated to be 10:1–20:1, instead of the optimal estimated ratio, which is 4:1 [ 147 ], a condition that is mainly due to the increasing abuse of vegetable oils (e.g., soy, safflower, corn, and sunflower) [ 142 , 148 , 149 ]. However, this ratio also seems to be influenced by personal genotype.…”
Section: Nutrigenomicsmentioning
confidence: 99%